Overdosage of HNF1B Gene Associated With Annular Pancreas Detected in Neonate Patients With 17q12 Duplication - Xiao, Feifan; Liu, Xiuyun; Lu, Yulan; Wu, Bingbing; Liu, Renchao; Liu, Bo; Yan, Kai; Chen, Huiyao; Cheng, Guoqiang; Wang, Laishuan; Ni, Qi; Li, Gang; et al. (Frontiers in Genetics, 2021)
The annular pancreas (AP) is a congenital anomaly of the pancreas that can cause acute abdominal pain and vomiting after birth. However, the genetic cause of AP is still unknown, and no study has reported AP in patients with 17q12 duplication. This study retrospectively analyzed the NGS data of individuals from Janurary 2016 to June 2020 for 17q12 duplication. To identify the function of the key gene of HNF1B in the 17q12 duplication region, human HNF1B mRNA was microinjected into LiPan zebrafish transgenic embryos. A total of 19 cases of 17q12 duplication were confirmed. AP was diagnosed during exploratory laparotomy in four patients (21.1%). The other common features of 17q12 duplication included intellectual disability (50%), gross motor delay (50%), and seizures/epilepsy (31.58%). The ratio of the abnormal pancreas in zebrafish was significantly higher in the HNF1B-overexpression models. In conclusion, we first reported AP in patients with duplication of the 17q12 region, resulting in the phenotype of 17q12 duplication syndrome. Furthermore, our zebrafish studies verified the role of the HNF1B gene in pancreatic development.